Method for producing optical laminate and intermediate laminate used therein

The method addresses peeling defects in liquid crystal film manufacturing by laminating a polarizer, adhesive, and retardation layer, and then peeling off the optical laminate from a supporting substrate using a peeling aid member, resulting in a high-quality optical laminate with minimal defects.

JP2025059822APending Publication Date: 2025-04-10NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023170146
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

The formation of liquid crystal films for optical laminates often results in peeling defects when the alignment substrate is removed, leading to appearance defects such as wrinkles and breakage in the optical laminate.

Method used

A method for manufacturing an optical laminate involving the lamination of a polarizer, an adhesive layer, and a retardation layer in that order, followed by peeling off the optical laminate from a supporting substrate using a peeling aid member, ensuring a stable and defect-free peeling process.

Benefits of technology

This method effectively suppresses appearance defects like wrinkles and breakage, resulting in an optical laminate with an extremely excellent appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059822000001_ABST
    Figure 2025059822000001_ABST
Patent Text Reader

Abstract

To provide a method for producing an optical laminate having excellent appearance.SOLUTION: Provided is a method for producing an optical laminate that includes a polarizer-containing polarizing plate, an adhesive layer, and a retardation layer, in this order, and the method comprises: laminating the polarizing plate with a laminate of the retardation layer and a support substrate via the adhesive layer to prepare an intermediate laminate; and bringing a peeling-assisting member into contact with the polarizing plate side of the intermediate laminate and peeling the optical laminate from the support substrate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an optical laminate, and an intermediate laminate used in the production method. [Background technology]

[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (for example, organic EL display devices and inorganic EL display devices), have rapidly become widespread. In many image display devices, optical laminates including retardation films are used. In recent years, as the demand for thinner image display devices has increased, the demand for thinner optical laminates has also increased. In order to reduce the thickness of optical laminates, the retardation layer (retardation film), which contributes greatly to the thickness, has been made thinner. A representative example of a thin retardation film is a film (hereinafter referred to as a liquid crystal film) in which a liquid crystal compound is oriented and the oriented state is fixed. Since the birefringence (Δn) of a liquid crystal compound is significantly larger than that of a resin, the thickness of the liquid crystal film to obtain a desired in-plane retardation can be made significantly smaller than that of a stretched film of a resin film. A liquid crystal film is typically formed by applying a composition including a liquid crystal compound to an alignment substrate and solidifying or curing the applied film. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-222282 A Summary of the Invention [Problem to be solved by the invention]

[0004] The formed liquid crystal film is laminated to a polarizing plate, and then the alignment substrate is peeled off and removed. However, peeling failure may occur when peeling the alignment substrate from the liquid crystal film. The present invention has been made to solve the above problems, and its main object is to provide a method for producing an optical laminate having excellent appearance. [Means for solving the problem]

[0005] 1. A manufacturing method for an optical laminate according to an embodiment of the present invention is a manufacturing method for an optical laminate including, in this order, a polarizing plate including a polarizer, an adhesive layer, and a retardation layer, and includes laminating the polarizing plate and a laminate of the retardation layer and a supporting substrate via the adhesive layer to produce an intermediate laminate, and contacting a peeling auxiliary member with the polarizing plate side surface of the intermediate laminate to peel the optical laminate from the supporting substrate. 2. In the method for producing an optical laminate described in 1 above, the peeling assistant member may be a peeling roll or a peeling bar. 3. In the method for producing an optical laminate according to the above 1 or 2, the retardation layer may be a layer in which a liquid crystal compound is aligned and solidified. 4. In the method for producing an optical laminate according to any one of the above items 1 to 3, the adhesive layer may be an adhesive layer. 5. In the method for producing an optical laminate described in any one of 1 to 4 above, the intermediate laminate may further include a surface protection film temporarily and releasably attached to the surface of the intermediate laminate facing the supporting substrate. 6. In the method for producing an optical laminate according to any one of 1 to 5 above, the adhesive layer may have a nanoindentation modulus of elasticity measured at 25° C. of 150 MPa or more. 7. In the method for producing an optical laminate according to any one of 1 to 6 above, the adhesive layer may have a nanoindentation hardness measured at 25° C. of 25 MPa or more. 8. In the method for producing an optical laminate according to any one of 1 to 7 above, the adhesive layer may have an elastic recovery rate at 25° C. of 75% or less as measured by nanoindentation. 9. In the method for manufacturing an optical laminate according to any one of 2 to 8 above, the diameter of the peeling roll may be 10 mm to 30 mm. 10. In another aspect of the present invention, an intermediate laminate is provided. This intermediate laminate is an intermediate laminate including a polarizing plate containing a polarizer, an adhesive layer, a retardation layer, and a support substrate in this order, and when peeling the laminate including the polarizing plate, the adhesive layer, and the retardation layer from the support substrate, the peeling force P1 by a 180° peeling test and the peeling force P2 by a 180° peeling test when peeling the support substrate from the laminate including the polarizing plate, the adhesive layer, and the retardation layer satisfy the relationship P1 < P2.

Advantages of the Invention

[0006] According to the present invention, it is possible to provide a method for manufacturing an optical laminate that suppresses appearance defects such as wrinkles and breakage and obtains an optical laminate with extremely excellent appearance.

Brief Description of the Drawings

[0007] [Figure 1] It is a partial schematic cross-sectional view of an intermediate laminate according to an embodiment of the present invention. [Diagram 2] It is a schematic view showing an example of a peeling step of an embodiment of the present invention. [Diagram 3] It is a schematic view showing another example of a peeling step of an embodiment of the present invention.

Modes for Carrying Out the Invention

[0008] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] The method for manufacturing an optical laminate according to an embodiment of the present invention is a method for manufacturing an optical laminate including a polarizing plate containing a polarizer, an adhesive layer, and a retardation layer in this order, and laminating a laminate of the polarizing plate, the retardation layer, and the support substrate via the adhesive layer to produce an intermediate laminate, and contacting a peeling auxiliary member with the surface on the polarizing plate side of the intermediate laminate and peeling the optical laminate from the support substrate. Hereinafter, each step will be described.

[0010] A. Intermediate laminate manufacturing process FIG. 1 is a partial schematic cross-sectional view of an intermediate laminate according to an embodiment of the present invention. The intermediate laminate 100 includes a polarizing plate 10 including a polarizer 11, an optical laminate 40 in which an adhesive layer 20 and a retardation layer 30 are laminated in this order, and a support substrate 50. The polarizing plate 10 typically includes a polarizer 11 and a protective layer 12 laminated on one surface of the polarizer. When another layer (for example, a retardation layer) included in the optical laminate also functions as a protective layer, the protective layer on the surface of the polarizer 11 on which the protective layer 12 is not laminated may be omitted. Although omitted in the illustrated example, a protective layer may be laminated on the surface of the polarizer 11 on which the protective layer 12 is not laminated. The adhesive layer 20 may be formed of any appropriate pressure-sensitive adhesive or adhesive. The retardation layer 30 may be a single layer or a laminate of two or more layers. The retardation layer may be an alignment solidified layer of a liquid crystal compound (hereinafter also referred to as a liquid crystal alignment solidified layer), or may be any appropriate resin film. If the retardation layer is a liquid crystal alignment solidified layer, a thinner optical laminate can be provided. The intermediate laminate 100 in the illustrated example further includes a surface protective film 60 temporarily attached to the support substrate 50 in a peelable manner. If the surface protective film 60 is further laminated, the support substrate 50 can be peeled off more stably. The intermediate laminate 100 is preferably long. If the intermediate laminate 100 is long, an optical laminate can be obtained efficiently. In addition, the obtained optical laminate is also long and can be wound into a roll. In this specification, the term "long" means a long and narrow shape whose length is sufficiently long relative to the width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, relative to the width.

[0011] When the intermediate laminate peels off a laminate (i.e., an optical laminate) including a polarizing plate, an adhesive layer, and a retardation layer from a support substrate, the peeling force P1 in a 180° peeling test and the peeling force P2 in a 180° peeling test when the support substrate peels off the laminate including the polarizing plate, the adhesive layer, and the retardation layer preferably satisfy the relationship P1 < P2. If P1 and P2 satisfy such a relationship, appearance defects such as wrinkles and breakage can be suppressed, and an optical laminate with extremely excellent appearance can be obtained. In this specification, P1 refers to the peeling force (N / 25 mm) measured by a 180° peeling test when a glass plate is laminated on the support substrate side of an intermediate laminate with a tape width of 25 mm and a tape length of 80 mm through an acrylic adhesive layer (thickness: 23 μm), and the optical laminate (i.e., the polarizing plate, the adhesive layer, and the retardation layer) is peeled off from the intermediate laminate at a peeling speed of 500 mm / min at 25°C. Also, P2 refers to the peeling force (N / 25 mm) measured by a 180° peeling test when a glass plate is laminated on the polarizing plate side of an intermediate laminate with a tape width of 25 mm and a tape length of 80 mm through an acrylic adhesive layer (thickness: 23 μm), and the support substrate is peeled off from the intermediate laminate at a peeling speed of 500 mm / min at 25°C.

[0012] It is preferable that the total thickness T1 of the laminate (i.e., the optical laminate) including the polarizing plate, the adhesive layer, and the retardation layer of the intermediate laminate and the total thickness T2 of the support substrate and the surface protection film temporarily adhered to the support substrate in a peelable manner satisfy the relationship T1 > T2. If T1 and T2 satisfy such a relationship, appearance defects such as wrinkles and breakage can be suppressed, and an optical laminate with extremely excellent appearance can be obtained.

[0013] A-1. Polarizing plate The polarizing plate 10 includes a polarizer 11 and a protective layer 12 laminated on at least one surface of the polarizer. If necessary, the polarizing plate 10 may include a protective layer on the side where the retardation layer 30 of the polarizer 11 is disposed.

[0014] A-1-1. Polarizer The polarizer 11 is typically a resin film containing a dichroic material (e.g., iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA)-based films, partially formalized PVA-based films, and partially saponified ethylene-vinyl acetate copolymer-based films.

[0015] The thickness of the polarizer is, for example, 18 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and further preferably 8 μm or less. The thickness of the polarizer is preferably 1 μm or more.

[0016] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 40.0% to 46.0%, preferably 41.0% to 45.0%, and more preferably 41.5% to 44.5%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0017] The polarizer may be produced by any appropriate method. Specifically, the polarizer may be produced from a single-layer resin film or may be produced by using a laminate including a substrate.

[0018] A method for producing a polarizer from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, etc. Such a production method is well known and commonly used in the art, so a detailed description thereof will be omitted.

[0019] The polarizer obtained by using the laminate containing the above-mentioned substrate can be produced, for example, by using a laminate of a resin substrate and a resin film or resin layer (typically, a PVA-based resin layer). Specifically, the polarizer can be produced by applying a PVA-based resin solution to a resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, preferably, a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, preferably, the laminate is subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of the present embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and high optical properties can be achieved. In addition, by simultaneously increasing the orientation of PVA in advance, problems such as a decrease in the orientation of PVA and dissolution can be prevented when immersed in water in the subsequent dyeing and stretching steps, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the PVA molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by shrinking the laminate in the width direction by the drying shrinkage treatment, high optical properties can be achieved. A polarizing plate can be obtained by laminating a protective layer on the peeled surface obtained by peeling the resin substrate from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeled surface. Details of such a method for producing a polarizer are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.

[0020] A-1-2.Protective layer The protective layer 12 may be formed of, for example, any appropriate resin film that can be used as a protective layer for a polarizer. Specific examples of the resin that is the main component of the resin film include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based resins, polyvinyl alcohol-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyethersulfone-based resins, polysulfone-based resins, polystyrene-based resins, cycloolefin-based resins such as polynorbornene, polyolefin-based resins, (meth)acrylic resins, and acetate-based resins.

[0021] The optical laminate 40 obtained by the manufacturing method according to the embodiment of the present invention is typically placed on the viewing side of an image display device, and the protective layer 12 is placed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat (HC) treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary.

[0022] The thickness of the protective layer is, for example, 5 μm to 80 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm. In addition, when the above-mentioned surface treatment is performed, the thickness of the protective layer includes the thickness of the surface treatment layer.

[0023] A-2. Retardation layer The retardation layer 30 typically has a circular polarization function or an elliptically polarizing function. The retardation layer may be a stretched polymer film (retardation film) or a layer of a liquid crystal compound with a solidified orientation (liquid crystal alignment solidified layer). The retardation layer may be a single layer or may have a laminated structure (substantially a two-layer structure). Preferably, the retardation layer is a liquid crystal alignment solidified layer. If the retardation layer is a liquid crystal alignment solidified layer, it can contribute to making the optical laminate thinner.

[0024] In one embodiment, the retardation layer includes a first liquid crystal alignment cured layer and a second liquid crystal alignment cured layer in order from the polarizer side. In this embodiment, the retardation layer as a whole (as a laminate of the first liquid crystal alignment cured layer and the second liquid crystal alignment cured layer) has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450) < Re(550) < Re(650). Hereinafter, this embodiment will be described in detail. In the following, regarding the description of the retardation layer in this section, simply referring to the "retardation layer" means describing it as a whole, and simply referring to the "liquid crystal alignment cured layer" means collectively describing the first liquid crystal alignment cured layer and the second liquid crystal alignment cured layer.

[0025] For the retardation layer, Re(550) is preferably 100 nm to 200 nm, more preferably 110 nm to 180 nm, still more preferably 120 nm to 170 nm, and particularly preferably 130 nm to 150 nm. If Re(550) of the retardation layer is within such a range, the retardation layer can exhibit a good circular polarization function or elliptical polarization function in combination with a polarizer.

[0026] The retardation layer preferably has a relationship of Re(450) < Re(550) < Re(650). That is, the retardation layer preferably exhibits an inverse dispersion wavelength dependence in which the retardation value increases according to the wavelength of the measurement light. With such a configuration, a good antireflection function can be realized in a very wide wavelength band. Re(450) / Re(550) is, for example, more than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and still more preferably 0.8 to 0.9. Re(650) / Re(550) is preferably 1.0 or more and less than 1.15, more preferably 1.03 to 1.1.

[0027] In one embodiment, the retardation layer may have an Nz coefficient of, for example, 0.30 to 0.70. Therefore, the retardation layer exhibits a refractive index characteristic of nx>nz>ny. With such a configuration, it is possible to effectively prevent reflection in oblique directions, and the anti-reflection function can be made to have a wide viewing angle. The Nz coefficient is preferably 0.35 to 0.65, more preferably 0.40 to 0.60, and further preferably 0.45 to 0.55.

[0028] Examples of the liquid crystal compound used in the liquid crystal alignment solidified layer include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable (i.e., liquid crystal monomer). If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it. Here, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal alignment solidified layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes that are specific to liquid crystal compounds. As a result, the liquid crystal alignment solidified layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.

[0029] In one embodiment, the liquid crystal alignment solidified layer may be formed using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and liquid crystal properties. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can be involved in a polymerization reaction by an active radical or acid generated from a photopolymerization initiator. As the liquid crystal monomer, for example, polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc., can be used. Specific examples of such polymerizable mesogenic compounds include LC242 (trade name) from BASF, E7 (trade name) from Merck, and LC-Sillicon-CC3767 (trade name) from Wacker-Chem.

[0030] The mechanism by which the liquid crystal compound exhibits liquid crystallinity may be thermotropic or lyotropic. The liquid crystal phase may be nematic or smectic. From the viewpoint of ease of production, the liquid crystallinity is preferably thermotropic nematic liquid crystal.

[0031] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0032] The birefringence Δn of the liquid crystal alignment solidified layer is preferably 0.06 or more, more preferably 0.08 or more, even more preferably 0.09 or more, and particularly preferably 0.10 or more. Δn can be, for example, 0.13 or less, and can also be, for example, 0.12 or less. If Δn is in such a range, a desired in-plane retardation can be realized with a very thin thickness. As a result, it becomes possible to further thin the liquid crystal alignment solidified layer and the optical laminate, which can ultimately contribute to a significant thinning of the image display device.

[0033] The liquid crystal alignment solidified layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value changes very little depending on the wavelength of the measurement light.

[0034] When the retardation layer has a laminated structure, the first liquid crystal alignment solidified layer can typically function as a λ / 2 plate, and the second liquid crystal alignment solidified layer can typically function as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal alignment solidified layer is preferably 150 nm to 300 nm, more preferably 200 nm to 270 nm, and even more preferably 220 nm to 260 nm; the Re(550) of the second liquid crystal alignment solidified layer is preferably 100 nm to 200 nm, more preferably 110 nm to 160 nm, and even more preferably 120 nm to 140 nm. The thickness of the first liquid crystal alignment solidified layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. In one embodiment, the thickness of the first liquid crystal alignment solidified layer can be, for example, 2.0 μm to 4.0 μm. In another embodiment, the thickness of the first liquid crystal alignment solidified layer is preferably 1.7 μm or less, more preferably 1.6 μm or less, and even more preferably 1.5 μm or less. In this case, the thickness of the first liquid crystal alignment solidified layer can be, for example, 1.3 μm or more. Thus, according to the embodiment of the present invention, the thickness of the first liquid crystal alignment solidified layer can be made thinner than before, while suppressing linear unevenness. The thickness of the second liquid crystal alignment solidified layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. Specifically, the thickness can be, for example, 0.8 μm to 2.5 μm. The angle between the slow axis of the first liquid crystal alignment solidified layer and the transmission axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 14° to 16°; the angle between the slow axis of the second liquid crystal alignment solidified layer and the transmission axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 74° to 76°. In addition, the order of arrangement of the first liquid crystal alignment solidified layer and the second liquid crystal alignment solidified layer may be reversed, and the angle between the slow axis of the first liquid crystal alignment solidified layer and the transmission axis of the polarizer and the angle between the slow axis of the second liquid crystal alignment solidified layer and the transmission axis of the polarizer may be reversed.

[0035] The refractive index of the liquid crystal alignment solidified layer can vary depending on the composition that forms the liquid crystal alignment solidified layer (substantially the type of liquid crystal compound, the type, number, combination, amount of additives, etc.). The refractive index n of the first liquid crystal alignment solidified layer LC1and the refractive index n of the second liquid crystal alignment solidified layer LC2 may be the same or different from each other (the refractive index n LC1 may be larger, and the refractive index n LC2 The refractive index n of the first liquid crystal alignment layer may be larger. LC1 The refractive index n of the second liquid crystal alignment solidified layer is preferably 1.55 to 1.75, and more preferably 1.60 to 1.70. LC2 The refractive index n of the first liquid crystal alignment solidified layer is preferably 1.45 to 1.65, and more preferably 1.50 to 1.60. LC1 and the refractive index n of the second liquid crystal alignment solidified layer LC2 The refractive index n of the first liquid crystal alignment solidified layer may be the opposite. LC1 and the refractive index n of the second liquid crystal alignment solidified layer LC2 The absolute value of the difference from the refractive index can be, for example, 0.00 to 0.20. The refractive index of the liquid crystal alignment solidified layer typically depends on the constitution of the composition forming the liquid crystal alignment solidified layer in order to obtain desired optical characteristics.

[0036] A side-chain type thermotropic liquid crystal polymer may be introduced into the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer (substantially the liquid crystal composition forming these). The introduction of a side-chain type thermotropic liquid crystal polymer can act to homeotropically align (vertically align) the liquid crystal monomer. As a result, the nz of the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer can be increased, and as a result, the Nz coefficient of the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer can be set to the desired range. Finally, the Nz coefficient of the retardation layer can be set to the desired range without providing a positive C plate described later.

[0037] As the side-chain type thermotropic liquid crystal polymer, typically, a copolymer having a monomer unit containing a thermotropic liquid crystal fragment side chain and a monomer unit containing a non-liquid crystal fragment side chain is used. When the polymer has a thermotropic liquid crystal fragment in the side chain, the side-chain type liquid crystal polymer can be aligned when the liquid crystal composition is heated to a predetermined temperature. When the side-chain type polymer has a non-liquid crystal fragment in the side chain, the non-liquid crystal fragment can interact with the photopolymerizable liquid crystal monomer to homeotropically align the photopolymerizable liquid crystal monomer.

[0038] As the side-chain type thermotropic liquid crystal polymer, a copolymer having a liquid crystalline monomer unit represented by general formula (I) and a non-liquid crystalline monomer unit represented by general formula (II) is preferably used. [ka] [ka]

[0039] In formula (I), R 1 is a hydrogen atom or a methyl group, and R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms; X 1 is -CO2- or -OCO-. a is an integer of 1 to 6, and b and c are each independently 1 or 2.

[0040] In formula (II), R 3 is a hydrogen atom or a methyl group, and R 4 is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III). [ka]

[0041] In formula (III), R5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.

[0042] The ratio of the liquid crystal monomer unit and the non-liquid crystal monomer unit in the side chain type liquid crystal monomer can be appropriately set according to the purpose. The ratio (molar ratio) of the non-liquid crystal monomer to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. With such a configuration, a liquid crystal alignment solidified layer exhibiting a desired refractive index characteristic (Nz coefficient) can be obtained.

[0043] The ratio of the liquid crystal monomer to the side-chain liquid crystal polymer in the liquid crystal composition can be appropriately set according to the purpose. When the content of the side-chain liquid crystal polymer is high, the Nz coefficient tends to be small, and when the content of the liquid crystal monomer is high, the Nz coefficient tends to be small. The content of the liquid crystal monomer is preferably 1.2 to 20 times, more preferably 1.3 to 10 times, still more preferably 1.4 to 9 times, and particularly preferably 1.5 to 8 times, the content of the side-chain liquid crystal polymer. With such a configuration, a liquid crystal alignment solidified layer exhibiting a desired refractive index characteristic (Nz coefficient) can be obtained.

[0044] Details of the side-chain liquid crystal polymer and the method for forming a liquid crystal alignment solidified layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921, the disclosure of which is incorporated herein by reference.

[0045] The retardation layer may further include a positive C plate. The positive C plate has a refractive index characteristic of nz>nx=ny. The positive C plate has a thickness retardation Rth(550) of preferably -20nm to -300nm, more preferably -30nm to -250nm, further preferably -40nm to -200nm, and particularly preferably -50nm to -150nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the positive C plate may be less than 10nm.

[0046] The positive C plate can be formed, for example, using a composition containing the above-mentioned side-chain liquid crystal polymer. Specific examples of the method for forming the positive C plate include the methods described in

[0020] to

[0028] of JP 2002-333642 A. In this case, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.

[0047] A-3. Supporting base material Any suitable substrate is used as the support substrate 50. Typically, a resin film is used. The retardation layer is laminated on the support substrate, which can improve the handleability of the retardation layer. When the retardation layer is a liquid crystal alignment solidified layer, the retardation film may be damaged during film transport in the manufacturing process due to its thin thickness. If the retardation layer is laminated on the support substrate, damage to the retardation layer during transport can be suppressed. In one embodiment, the support substrate may be an alignment substrate for the retardation layer, which is a liquid crystal alignment solidified layer. That is, a liquid crystal composition forming a liquid crystal alignment solidified layer is applied to the support substrate, and the liquid crystal compound in the composition is aligned by the alignment regulating force of the support substrate, and the liquid crystal compound is solidified or cured in an aligned state to form a liquid crystal alignment solidified layer. The intermediate laminate 100 can be obtained by laminating the laminate of the support substrate 50 and the retardation layer 30, which is a liquid crystal alignment solidified layer, and the polarizing plate 10 via the adhesive layer 20. The support substrate 50 can be peeled off and removed in a later process. That is, the support substrate 50 is peelably laminated on the retardation layer 30. When the retardation layer has a laminated structure, it is preferable to use a substrate similar to the substrate 50 as the alignment substrate of the first liquid crystal alignment solidified layer and the second liquid crystal alignment solidified layer.

[0048] The tensile modulus of the support substrate 50 is preferably 3000 N / mm 2 That is all. With this configuration, peeling failure when peeling off the support substrate can be suppressed. Specifically, peeling off of the retardation layer together with the substrate can be prevented or effectively suppressed. The tensile modulus of the support substrate is preferably 4000 N / mm 2 More preferably, it is 5000N / mm 2 More preferably, it is 6000N / mm 2 More preferably, it is 6500N / mm 2 On the other hand, the tensile modulus of the substrate is, for example, 9000 N / mm 2 It may be less than or equal to 8500 N / mm 2 The tensile modulus can be determined in accordance with JIS K 7161.

[0049] The peeling force of the support substrate is preferably 1.2N / 50mm or less, more preferably 1.0N / 50mm or less, even more preferably 0.8N / 50mm or less, and particularly preferably 0.7N / 50mm or less. On the other hand, the peeling force of the support substrate can be, for example, 0.01N / 50mm or more, and can be, for example, 0.02N / 50mm or more. With such a configuration, peeling failure when peeling the support substrate can be suppressed. Specifically, peeling of the retardation layer together with the support substrate can be prevented or effectively suppressed.

[0050] The support substrate may be an alignment substrate of the retardation layer, which is a liquid crystal alignment solidified layer, as described above. Therefore, the support substrate may have an alignment regulating force. The alignment regulating force can be given by, typically, rubbing alignment, stretching substrate alignment, or photo-alignment. Preferably, it is stretching substrate alignment or photo-alignment.

[0051] The supporting substrate may have any suitable structure. Specifically, the supporting substrate may be a single film, or may have a laminated structure of two or more layers (may be a laminate). As described above, the supporting substrate is typically composed of a resin film. Therefore, the supporting substrate may be a single resin film, or may be a laminate including a first resin film and a second resin film. A single film may be excellent in cost and versatility. When a single film cannot achieve both a desired orientation restricting force and a desired tensile modulus, a laminate can achieve both properties by complementing these properties with a plurality of resin films. The laminate may be a three-layer laminate further including a third resin film, a four-layer laminate further including a fourth resin film, or a five-layer or more laminate. Each resin film included in the laminate is typically laminated via a pressure-sensitive adhesive layer.

[0052] Representative materials constituting the resin film include cellulose resins such as TAC, cycloolefin resins such as polynorbornene, (meth)acrylic resins, polyester resins such as PET and PEN, polyolefin resins such as polyethylene and polypropylene, and polycarbonate resins.Specific configurations of the substrate preferably include a single film of a TAC film having an orientation control force, and a laminate having a configuration of a TAC film having an orientation control force / adhesive layer / PET film.

[0053] The thickness of the substrate may vary depending on the material of the substrate, the structure of the substrate, etc. The thickness of the substrate may be, for example, 20 μm or more, for example, 25 μm or more, for example, 30 μm or more, for example, 35 μm or more, or for example, 40 μm or more. On the other hand, the thickness of the substrate may be, for example, 120 μm or less, for example, 110 μm or less, or for example, 100 μm or less.

[0054] A-4.Adhesive layer The adhesive layer 20 is formed of any appropriate adhesive or bonding agent. Specific examples of adhesives include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. Only one type of base resin of the adhesive may be used, or two or more types may be used in combination. When the adhesive layer is an adhesive layer, the thickness of the adhesive layer is preferably 1 μm to 30 μm, more preferably 2 μm to 20 μm, and even more preferably 3 μm to 15 μm.

[0055] A representative example of the adhesive is an active energy ray curable adhesive. By using an active energy ray curable adhesive as the adhesive, the adhesive layer can be thinned, and as a result, an optical laminate with excellent flexibility can be obtained. Furthermore, the adhesive layer can be made high in refractive index, and the difference in refractive index with the adjacent liquid crystal alignment solidified layer can be reduced. As a result, reflection at the interface between the first adhesive layer and the first liquid crystal alignment solidified layer is suppressed, and an optical laminate with excellent anti-reflection performance can be obtained. The active energy ray curable adhesive can be selected from radical curable, cationic curable, anionic curable, and the like as needed, and can be used in appropriate combination, such as a hybrid of radical curable and cationic curable. The radical curable adhesive can be, for example, an adhesive containing a compound (e.g., monomer and / or oligomer) having a radical polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group as a curing component. As for the active energy ray curable adhesive, the type, combination, and compounding ratio of the double bond-containing monomer and / or oligomer, crosslinking agent, etc. can be adjusted to obtain an active energy ray curable adhesive having desired properties (e.g., storage modulus after curing). Examples of the active energy ray include ultraviolet light, visible light, infrared light, and electron beams. The ultraviolet ray curable adhesive is preferred because it has excellent versatility and ease of handling. Note that the active energy ray curable adhesive is well known in the industry, so a detailed description of the composition is omitted.

[0056] When the adhesive layer is an adhesive layer, the thickness of the adhesive layer is preferably 0.1 μm to 3.0 μm, more preferably 0.5 μm to 2.0 μm, and further preferably 0.8 μm to 1.5 μm. Such a thickness can contribute to making the optical laminate thinner.

[0057] A-5. Surface protection film As described above, the intermediate laminate may further have a surface protection film temporarily attached in a releasable manner to the supporting substrate side. The surface protection film typically includes a substrate layer and a pressure-sensitive adhesive layer. The surface protection film is temporarily attached in a releasable manner to the supporting substrate side of the intermediate laminate via the pressure-sensitive adhesive layer.

[0058] A-5-1. Base material layer The substrate layer is, for example, a resin film. Examples of the constituent materials of the resin film include polyester, polyolefin, polyamide, polyimide, polycarbonate, polyacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, and polyfluoroethylene. Examples of polyester include polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate. Examples of polyolefin include polyethylene, polypropylene, polybutene, polymethylpentene, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, and ethylene-vinyl alcohol copolymer. Examples of polyamide include nylon 6, nylon 6,6, and partially aromatic polyamide. The substrate layer may be made of one type of material, or may be made of two or more types of materials. The substrate layer may have a single layer structure or a multilayer structure. In addition, when the substrate layer is a resin film, the substrate layer may be a stretched film or a non-stretched film.

[0059] The thickness of the substrate layer is, for example, 10 μm to 200 μm, preferably 15 μm to 150 μm, more preferably 20 μm to 100 μm, and further preferably 25 μm to 75 μm. When the thickness is within the above range, the strength as a support in the surface protection film can be ensured, and a surface protection film having appropriate flexibility can be obtained.

[0060] The tensile modulus of the substrate is preferably 1.0×10 8 Pa~1.0×10 10 Pa, more preferably 1.0×10 9Pa~1.0×10 10 When the tensile modulus of the substrate is within the above range, the workability of peeling and removing the support substrate from the intermediate laminate can be improved. The tensile modulus of elasticity is measured in accordance with JIS K 7161.

[0061] The elastic modulus of the substrate is, for example, 2.2 kN / mm 2 ~4.8kN / mm 2 If the elastic modulus of the substrate is within this range, deformation during transportation and / or lamination can be suppressed. In addition, the workability of peeling and removing the support substrate from the intermediate laminate can be improved. The elastic modulus is measured in accordance with JIS K 6781.

[0062] A-5-2. Adhesive layer for surface protection film The adhesive layer (adhesive layer for surface protective film) may be formed of any suitable adhesive. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, etc., an adhesive having desired properties according to the purpose can be prepared. Only one type of base resin of the adhesive may be used. Two or more types may be used in combination. The base resin is preferably an acrylic resin (i.e., the adhesive layer is preferably composed of an acrylic adhesive).

[0063] The thickness of the pressure-sensitive adhesive layer of the surface protection film is preferably 3 μm to 100 μm, more preferably 4 μm to 60 μm, further preferably 5 μm to 40 μm, and particularly preferably 10 μm to 25 μm.

[0064] A-6. Lamination of polarizing plate and retardation layer The polarizing plate and the laminate of the retardation layer and the support substrate are laminated via the pressure sensitive adhesive or adhesive that forms the adhesive layer. The adhesive layer can be formed by any suitable method. For example, when the adhesive layer is an adhesive layer, preferred methods for forming the adhesive layer include gravure coating and slot die coating.

[0065] In one embodiment, the intermediate laminate is long. The long intermediate laminate can be obtained, for example, by laminating a long polarizing plate and a laminate of a long retardation layer and a support base material. If a long polarizing plate and a laminate of a long retardation layer and a support base material are used, lamination can be performed by roll-to-roll, and productivity can be improved. Typically, a laminate of a long retardation layer and a support base material is laminated on a long polarizing plate so that the longitudinal directions of the two are aligned.

[0066] B. Support base material peeling process Next, the support substrate 50 laminated on the retardation layer 30 is peeled off from the intermediate laminate 100. By peeling off the support substrate from the intermediate laminate, the optical laminate 40 can be obtained. In the manufacturing method of the embodiment of the present invention, a peeling assistant member is brought into contact with the polarizing plate side surface of the intermediate laminate, and the optical laminate is peeled off from the support substrate. In general, in the manufacturing method of the optical laminate, tension is applied to the support substrate to peel it off from the intermediate laminate. In the manufacturing method of the embodiment of the present invention, a peeling member is brought into contact with the polarizing plate side surface of the intermediate laminate, and tension is applied to the optical laminate to peel it off. According to the manufacturing method of the embodiment of the present invention, an optical laminate with excellent appearance can be provided by suppressing appearance defects such as wrinkles and breakage.

[0067] The intermediate laminate is peeled off such that the angle α between the surface of the intermediate laminate immediately before peeling and the peeling direction of the optical laminate is smaller than the angle β between the surface of the intermediate laminate immediately before peeling and the peeling direction of the optical laminate. According to such an embodiment, it is possible to suppress appearance defects such as wrinkles and breakage, and to satisfactorily peel the support substrate from the optical laminate. As a result, an optical laminate with extremely excellent appearance can be provided.

[0068] The difference between the angle β and the angle α is preferably 60° or more, and more preferably 90° to 180°. The angle α is preferably 30° or less, and more preferably 0° to 20°. The angle β is preferably 60° or more, and more preferably 90° to 180°.

[0069] The tension required for the above peeling (peeling tension) is preferably 300N or less, more preferably 200N or less, and further preferably 100N or less.

[0070] 2 is a schematic diagram showing an example of a peeling step according to an embodiment of the present invention. The intermediate laminate 100 is transported so that the support substrate 50 is in contact with a transport roller, and a peeling assistant member 70 is brought into contact with the polarizing plate side surface of the intermediate laminate 100 (in the illustrated example, the surface not in contact with the support substrate 50 of the optical laminate 40). In the illustrated example, the peeling assistant member 70 is a triangular prism-shaped peeling bar. In the illustrated example, while transporting the intermediate laminate 100 in the upward direction, the peeling bar is brought into contact with the polarizing plate side surface of the intermediate laminate 100 (in the illustrated example, the surface not in contact with the support substrate 50 of the optical laminate 40), and the optical laminate 40 is pulled downward, whereby the optical laminate 40 is peeled off from the intermediate laminate 100, and the support substrate 50 is transported in the upward direction.

[0071] FIG. 3 is a schematic diagram showing another example of the peeling step of the embodiment of the present invention. In this illustrated example, a peeling roll is used as a peeling auxiliary member. In this illustrated example, the peeling roll is brought into contact with the polarizing plate side surface of the intermediate laminate 100 (the surface of the optical laminate 40 that is not in contact with the support substrate 50 in the illustrated example) while conveying the intermediate laminate 100 in the upward direction, and the optical laminate 40 is pulled downward, whereby the optical laminate 40 is peeled off from the intermediate laminate 100, and the support substrate 50 is conveyed upward. When a peeling roll is used, the roll diameter is preferably 5 mm to 80 mm, more preferably 5 mm to 50 mm, and further preferably 10 mm to 30 mm. If the roll diameter is too large, the peel strength becomes large, and good peeling may not be performed. If the roll diameter is too small, the strength of the roll may be insufficient, and the peel stability may be insufficient.

[0072] The adhesive layer preferably has a nanoindentation modulus of 150 MPa or more, more preferably 300 MPa or more, even more preferably 500 MPa or more, and particularly preferably 600 MPa or more, measured at 25°C. If the nanoindentation modulus is within the above range, the support substrate can be peeled off well from the intermediate laminate. The nanoindentation modulus is, for example, 1200 MPa or less. In this specification, the nanoindentation modulus of the adhesive layer refers to a value measured by the following method. The optical laminate is cut into 1 cm square and fixed to a support to be used as a measurement sample. The sample is set on the stage of a nanoindenter (for example, manufactured by Hysitron, product name "Triboindenter"), and a single indentation measurement is performed at a measurement temperature of 25°C using a Berkovich (triangular pyramid) type indenter. Specifically, the indenter is pressed from the retardation layer side of the optical laminate including the polarizing plate and the retardation layer toward the adhesive layer to a maximum indentation depth of 1000 nm at a pressing speed of 200 nm / sec, and is pulled out at a pulling speed of 200 nm / sec. The nanoindentation elastic modulus is calculated from the load acting between the indenter and the sample and the relative displacement of the indenter with respect to the sample, which are measured during the process of pressing the indenter into the sample (load application process) and the process of subsequently pulling the indenter out of the sample (unloading process) (load-displacement measurement). Specifically, the nanoindentation elastic modulus is calculated from the load at the deepest pressing (maximum load Pmax) and the area of ​​contact between the indenter and the sample (contact projected area A) using the following formula. Nanoindentation hardness (MPa) = Pmax / A

[0073] The nanoindentation hardness of the adhesive layer measured at 25°C is preferably 25 MPa or more, more preferably 30 MPa or more, even more preferably 40 MPa or more, and particularly preferably 50 MPa or more. If the nanoindentation hardness is within the above range, the support substrate can be favorably peeled off from the intermediate laminate. The nanoindentation hardness is, for example, 100 MPa or less. In this specification, the nanoindentation hardness of the adhesive layer refers to a value calculated from the following formula using the value measured by the above method. It is calculated by applying the slope of the tangent of the unloading curve of the load-displacement curve obtained by the load-displacement measurement of the nanoindentation measurement (contact stiffness S) and the above contact projected area A to the following formula. Nanoindentation modulus (MPa) = (√π×S) / (2×√A)

[0074] The nanoindentation elastic recovery of the adhesive layer measured at 25°C is preferably 75% or less, more preferably 70% or less, and even more preferably 65% ​​or less. If the nanoindentation elastic recovery is within the above range, the support substrate can be favorably peeled off from the intermediate laminate. The nanoindentation elastic recovery is, for example, 40% or more. In this specification, the nanoindentation elastic recovery of the adhesive layer refers to a value measured by the following method. It refers to a value calculated by the following formula from the displacement amount (maximum displacement, hmax) and the plastic deformation amount (hf) when the adhesive layer is pressed deepest, obtained by the nanoindentation measurement. Nanoindentation elastic recovery rate = (hmax-hf) / hmax EXAMPLES

[0075] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows.

[0076] 1. Thickness The measurement was performed using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C").

[0077] 2. Nanoindentation Measurements The optical laminates obtained in the Examples, Comparative Examples, and Reference Examples were cut into 1 cm squares and fixed to a support (a slide glass manufactured by Matsunami Glass Industry Co., Ltd., with a thickness of 0.8 mm to 1.0 mm) so that the polarizing plate side of the optical laminate and the support were in contact with each other, and used as measurement samples. The sample was set on the stage of a nanoindenter (manufactured by Hysitron, product name "Triboindenter"), and a single indentation measurement was performed at a measurement temperature of 25°C using a Berkovich (triangular pyramid) indenter. Specifically, the indenter was pressed from the retardation layer side of the optical laminate including the polarizing plate and the retardation layer toward the adhesive layer to a maximum indentation depth of 1000 nm at a pressing speed of 200 nm / sec, and pulled out at a pulling speed of 200 nm / sec. The load acting between the indenter and the sample, measured during the process of pressing the indenter into the sample (load application process) and the subsequent process of pulling the indenter out of the sample (unloading process), and the load-displacement curve obtained from the relative displacement of the indenter with respect to the sample were used to calculate the nanoindentation hardness, nanoindentation elastic modulus, and nanoindentation elastic recovery rate according to the following formula. Measurements were performed on three samples, and the average values ​​were used as the results for each sample. Nanoindentation hardness (GPa) = (load at deepest indentation: Pmax) / (area of ​​contact between indenter and sample (contact projected area A)) Nanoindentation elastic modulus (GPa) = (√π × (slope of the tangent to the unloading curve of the load-displacement curve (contact stiffness S))) / (2 × √contact projected area A) Nanoindentation elastic recovery rate = (displacement at deepest indentation (maximum displacement hmax) - plastic deformation (hf)) / maximum displacement hmax

[0078] 3. Peeling force The intermediate laminates prepared in Production Examples 1 and 2 were cut to a tape width of 25 mm and a length of 80 mm to be used as samples. The support substrate side of the sample was laminated on a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., thickness 1.3 mm) via an acrylic adhesive layer (thickness 23 μm), and the optical laminate (i.e., polarizing plate, adhesive layer, and retardation layer) was peeled off from the intermediate laminate at a peeling speed of 500 mm / min at 25°C to perform a 180° peeling test and measure the peeling force. In addition, the polarizing plate side of the sample was laminated on a glass plate via an acrylic adhesive layer (thickness 23 μm), and similarly performed a 180° peeling test to measure the peeling force (N / 25 mm).

[0079] [Production Example 1] Preparation of intermediate laminate 1 1. Preparation of Polarizing Plates 1-1. Preparation of polarizer A polyvinyl alcohol film having an average polymerization degree of 2,400, a saponification degree of 99.9 mol%, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was stretched 2.2 times in the conveying direction while swelling by immersing in a swelling bath (water bath) at 20 ° C. between rolls with different peripheral speed ratios (swelling step), and then stretched 3.3 times in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film not stretched at all in the conveying direction) while dyeing by immersing in a dyeing bath (aqueous solution with an iodine concentration of 0.1 wt % and a potassium iodide concentration of 0.9 wt %) at 30 ° C. (dyeing step). Next, the dyed polyvinyl alcohol film was immersed in a crosslinking bath (aqueous solution with a boric acid concentration of 3.0 wt % and a potassium iodide concentration of 3.0 wt %) at 40 ° C. for 28 seconds to stretch 3.6 times in the conveying direction based on the original polyvinyl alcohol film (crosslinking step). The obtained polyvinyl alcohol film was then immersed in a 61°C stretching bath (aqueous solution with a boric acid concentration of 4.0% by weight and a potassium iodide concentration of 5.0% by weight) for 60 seconds to stretch the film to 6.0 times the original polyvinyl alcohol film in the conveying direction (stretching step), and then immersed in a 20°C washing bath (aqueous solution with a potassium iodide concentration of 2.0% by weight) for 10 seconds (washing step). The washed polyvinyl alcohol film was dried at 40°C for 30 seconds to produce a polarizer. The polarizer had a thickness of 18 μm.

[0080] 1-2. Preparation of polarizing plate As the adhesive, an aqueous solution containing a polyvinyl alcohol resin containing an acetoacetyl group (average polymerization degree 1,200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylolmelamine in a weight ratio of 3:1 was used. Using this adhesive, a 30 μm thick transparent protective film (manufactured by Nippon Shokubai Co., Ltd.) made of a (meth)acrylic resin (modified acrylic polymer having a lactone ring structure) was laminated as a protective layer on one side (display element side) of the polarizer obtained above, and a 49 μm thick transparent protective film made of a triacetyl cellulose film (manufactured by Fuji Film Co., Ltd., product name "TJ40UL") with HC was laminated as a protective layer on the other side (viewing side) using a roll laminator, and then the film was heated and dried in an oven (temperature 90°C, time 10 minutes) to produce a polarizing plate in which the transparent protective film was laminated on both sides of the polarizer. The single transmittance of the obtained polarizer was 41.7%, and the polarization degree was 99.9%.

[0081] 2. Preparation of retardation layer A photopolymerizable liquid crystal compound exhibiting a nematic liquid crystal phase (BASF's "Paliocolor LC242", chemical formula below) was dissolved in cyclopentanone to prepare a solution with a solids concentration of 20% by weight. A leveling agent (DIC's "Megafac F-563"), a photopolymerization initiator (IGM Resins' "Omnirad907") and a crosslinking agent (Shin-Nakamura Chemical Co., Ltd.'s "A-DCP") were added to this solution to prepare a coating liquid for forming a liquid crystal alignment solidified layer. A TAC film (thickness: 80 μm, tensile modulus: 3391 N / mm 2 The above-mentioned liquid crystal alignment solidified layer forming coating solution was applied onto this supporting substrate by a spin coater, and the liquid crystal compound was aligned by heating at 100°C for 3 minutes. After cooling to room temperature, the substrate was exposed to an integrated light dose of 600 mJ / cm2 in a nitrogen atmosphere. 2 The alignment state of the liquid crystal compound was fixed by irradiating the film with ultraviolet light of 1000 nm to perform photocuring. In this manner, a laminate of a supporting substrate / liquid crystal alignment solidified layer (thickness: 2 μm, Re(550): 270 nm) was obtained. [ka]

[0082] 3. Preparation of Adhesive A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 1 part by weight of 4-hydroxybutyl acrylate (HBA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C and a polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction liquid to prepare a solution of a (meth)acrylic polymer with a weight average molecular weight of 2 million, adjusted to a solid content concentration of 30%. An acrylic adhesive composition was prepared by blending 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, product name "Coronate L") and 0.1 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM403") with 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.

[0083] 4. Preparation of Optical Laminate A liquid crystal alignment solidified layer was attached to the TAC film surface on the opposite side to the HC layer of the polarizing plate via an adhesive layer (thickness 12 μm) formed using the pressure-sensitive adhesive obtained above, to obtain an intermediate laminate 1.

[0084] [Production Example 2] Preparation of intermediate laminate 2 1. Preparation of Adhesive Composition 20 parts by weight of unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone (manufactured by Daicel Corporation, trade name "Placcel FA1DDM"), 20 parts by weight of acryloyl morpholine (manufactured by Kohjin Co., Ltd., trade name "ACMO"), 3 parts by weight of diethyl acrylamide (manufactured by KJ Chemicals, trade name "DEAA"), 6.7 parts by weight of lauryl acrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Light Acrylate LA"), 27 parts by weight of isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "ISTA"), 10 parts by weight of 1,9-nonanediol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Light Acrylate 1,9ND-A"), acrylic oligomer (manufactured by Toagosei Co., Ltd., trade name "ARUFON An adhesive composition was prepared by stirring 13.3 parts by weight of an initiator (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one) (manufactured by IGM Resins BV, product name "Omnirad 907"), and 3 parts by weight of a photopolymerization accelerator (diethylthioxanthone) (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE DETX-S") at 50°C for 1 hour.

[0085] An intermediate laminate 2 was obtained in the same manner as in Production Example 1, except that an adhesive layer (thickness: 1.2 μm) was formed using the above adhesive instead of the pressure-sensitive adhesive.

[0086] [Example 1] The intermediate laminate 1 was placed on a flat table with the support substrate facing downward. A peeling roll (diameter 20 mm) was brought into contact with the polarizing plate side surface of the intermediate laminate as a peeling auxiliary member. The end of the optical laminate (HC layer / TAC film (protective layer) / polarizer / acrylic film (protective layer) / adhesive layer / retardation layer) included in the intermediate laminate was peeled upward along the peeling roll to peel the optical laminate from the support substrate, thereby obtaining an optical laminate. Table 1 shows the nanoindentation measurement results and the appearance evaluation results of the obtained optical laminate.

[0087] [Example 2] An optical laminate was obtained in the same manner as in Example 1, except for using the intermediate laminate 2. Table 1 shows the results of the nanoindentation measurement and the appearance evaluation of the obtained optical laminate.

[0088] (Comparative Example) An optical laminate was obtained in the same manner as in Example 2, except that the intermediate laminate 2 was placed with the hard coat layer side of the polarizing plate facing downward. The nanoindentation measurement results and the appearance evaluation results of the obtained optical laminate are shown in Table 1.

[0089] (Reference example) Except for placing the intermediate laminate 1 with the hard coat layer side of the polarizing plate facing downward, an optical laminate was obtained in the same manner as in Example 1. The nanoindentation measurement results and the appearance evaluation results of the obtained optical laminate are shown in Table 1.

[0090] [evaluation] The appearance of the optical laminates obtained in each of the Examples, Comparative Examples, and Reference Examples was evaluated visually. The evaluation criteria for appearance were as follows: (Appearance Evaluation Criteria) Good: The resin substrate could be peeled off continuously in the longitudinal direction, and no wrinkles or foreign matter (e.g., substrate residue) were found in the obtained polarizing plate. Defective: Continuous peeling was difficult, and wrinkles and foreign matter occurred in the resulting polarizing plate.

[0091] [Table 1] [Industrial Applicability]

[0092] The optical laminate obtained by the manufacturing method according to the embodiment of the present invention is suitably used in image display devices such as liquid crystal display devices and organic electroluminescence display devices. [Explanation of symbols]

[0093] 10 Polarizing plate 11 Polarizer 12 Protective layer 20 Adhesive layer 30 Retardation layer 40 Optical laminate 50 Supporting base material 60 Surface protection film 70 Peeling aid 100 Intermediate laminate

Claims

1. A method for producing an optical laminate including a polarizing plate including a polarizer, an adhesive layer, and a retardation layer in this order, comprising: laminating the polarizing plate and a laminate of the retardation layer and the supporting substrate via the adhesive layer to produce an intermediate laminate; bringing a peeling assistant member into contact with a surface of the intermediate laminate facing the polarizing plate, and peeling the optical laminate from the supporting substrate.

2. The method according to claim 1 , wherein the peeling aid member is a peeling roll or a peeling bar.

3. The method according to claim 1 , wherein the retardation layer is a layer in which a liquid crystal compound is aligned and fixed.

4. The method of claim 1 , wherein the adhesive layer is an adhesive layer.

5. The method according to claim 1 , further comprising laminating a surface protection film, which is temporarily and releasably attached to the surface of the intermediate laminate facing the supporting substrate.

6. The method according to claim 1 , wherein the adhesive layer has a nanoindentation elastic modulus of 150 MPa or more measured at 25° C.

7. The method according to claim 1 , wherein the adhesive layer has a nanoindentation hardness of 25 MPa or more measured at 25° C.

8. The method according to claim 1 , wherein the adhesive layer has an elastic recovery of 75% or less at 25° C. as measured by nanoindentation.

9. The method according to claim 2, wherein the diameter of the peeling roll is 10 mm to 30 mm.

10. An intermediate laminate including a polarizing plate including a polarizer, an adhesive layer, a retardation layer, and a supporting substrate in this order, A peel force P in a 180° peel test when peeling a laminate including the polarizing plate, the adhesive layer, and the retardation layer from the supporting substrate. 1 and a peel force P in a 180° peel test when peeling the support substrate from a laminate including the polarizing plate, the adhesive layer, and the retardation layer. 2 Toga P 1 <P 2 The intermediate laminate satisfies the relationship:

Citation Information

Patent Citations

  • Polaroid tearing mechanism and polaroid tearing method

    CN113325617A

  • Transfer body for optical film, optical film, image display device, manufacturing method of transfer body for optical film, and manufacturing method of optical film

    JP2014222282A

  • Method for manufacturing polarizing plate

    JP2015034960A

  • Peeling method

    JP2018020866A

  • Long-sized liquid crystal cured layer laminated film

    JP2021124641A